MTW-OPAL: a technology development platform for ultra-intense optical parametric chirped-pulse amplification systems. (6th October 2021) - Bromage, J.; Bahk, S.-W.; Bedzyk, M.; Begishev, I. A.; Bucht, S.; Dorrer, C.; Feng, C.; Jeon, C.; Mileham, C.; Roides, R. G.; Shaughnessy, K.; Shoup, M. J.; et al.
Abstract: Optical parametric chirped-pulse amplification implemented using multikilojoule Nd:glass pump lasers is a promising approach for producing ultra-intense pulses (>10 23 W/cm 2 ). We report on the MTW-OPAL Laser System, an optical parametric amplifier line (OPAL) pumped by the Nd:doped portion of the multi-terawatt (MTW) laser. This midscale prototype was designed to produce 0.5-PW pulses with technologies scalable to tens of petawatts. Technology choices made for MTW-OPAL were guided by the longer-term goal of two full-scale OPALs pumped by the OMEGA EP to produce 2 × 25-PW beams that would be co-located with kilojoule−nanosecond ultraviolet beams. Several MTW-OPAL campaigns that have been completed since "first light" in March 2020 show that the laser design is fundamentally sound, and optimization continues as we prepare for "first-focus" campaigns later this year.